Enigmes de la Deuxième épître de Paul aux Corinthiens é́tude exégétique de 2 Cor. 2:14-7:4 - Collange, Jean-François 1944- (Cambridge Cambridge University Press, 2005)
Paul's Second Epistle to the Corinthians poses exegetical problems of well-known difficulty. The structure and unity of the whole Epistle are in doubt, as is the meaning of many particular passages and references - for example, the identity of Paul's opponents. Dr Collange bases his solutions to these problems on a detailed study of 2,14 - 7,4. He argues that the obscurities of the Epistle can be explained by the particular circumstances of its composition; Paul's use of more primitive Christian materials gives us a measure of his own originality and genius. This book should be of interest to all New Testament scholars.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible -- Commentaries; Bible -- Commentaries; Bible // N.T. // Corinthians 2, II, 14 - VII, 4 -- Commentaries; Bible ; Corinthians, 2nd, II, 14-VII, 4 ; Commentaries; Kommentar